Institutional and Programme Accreditation, Quality Audits and Academic Reviews as Quality Assurance Mechanisms in Higher Education - Pinias, Chikuvadze; Young, Mudavanhu; Diamond, Dziva; Claretah, Makuvire; Joseph, Zuva (Quality Assurance Practices for Transformative Higher Education in Southern Africa, 2025)
Higher education in most developing countries is going through expansion as a result of increased competition, limited resources, mass education and accountability to other stakeholders. All these have raised concerns about the quality of education in institutions of higher learning. In other instances, this at times unplanned and chaotic expansion has resulted in a decline in the quality of higher education that could have serious consequences. In this regard, most Southern African countries, which include Angola, Botswana, Eswatini, Lesotho, Malawi, Mozambique, Namibia, South Africa, Zambia, and Zimbabwe, advocated for mechanisms to improve the quality of higher education. Therefore, this chapter explores the role of institutional and programme accreditation, quality audits, and academic reviews as essential quality assurance mechanisms in higher education. The literature review approach guides the review of existing research and literature at the centre of this chapter. This aims to provide a comprehensive and evidence-based discourse. Hence, it interrogates the processes and standards involved in institutional and programme accreditation, highlighting their significance in ensuring academic excellence, compliance with educational standards, and fostering continuous improvement. In addition, the examination of the accreditation processes and standards reveals significant challenges, maintaining consistency and equity across higher education institutions. This underscores the need for a more transparent and adaptable accreditation framework to address evolving stakeholder needs. Further to this, the chapter delves into quality audits and academic reviews as tools for evaluating institutional performance, effectiveness, and alignment with strategic goals. Through analysis, it looks at the impact of these mechanisms on enhancing teaching and learning, maintaining institutional reputation, and meeting the needs of diverse stakeholders. Finally, the chapter considers the challenges and opportunities associated with these quality assurance practices in a dynamic higher education landscape. The chapter concludes by recommending the adoption of a standardised accreditation framework to address discrepancies and ensure equitable implementation across higher education institutions. Additionally, it advocates for stakeholder engagement in the design of accreditation standards to enhance transparency and adaptability to both the regional and local contexts. Thus, this chapter emphasises the importance of improving accreditation, audits and academic review processes, highlighting how streamlined and transparent standards can empower practitioners to enhance institutional quality.